Perhitungan Struktur Atas Jembatan Beton Bertulang Balok T Desa Sebulu Ilir Kecamatan Sebulu Kabupaten Kutai Kartanegara - JANUARDI, RICKY (KURVA S JURNAL MAHASISWA, 2013)
Planner process a structure constitute a process a directed and detailed,repeated, and coherently according to funcition, layout, use of building to construted.. In the implementation in the field occurred several times repositioning, so based on the layout of the building will affect the condition of the building structure planning. Location of concrete bridge development planning activities of kampung sebulu, located on pemuda street sebulu ulu. based on the data collected by the way sekunder of the data is required to support primary data obtained from studies literature, The collection of data and data collected directly in field.This thesis done in the design and analysis of structure Division. On the process of the slab obtained thick slab 200, thick asphalt 100, reinforcement negative reinforcement obtained bending D19-150 and reinforcement positive reinforcement obtained bending D19-150. Design T-girder, girder was high 1,200 m, girder width 0,600 m, used tensile reinforcement 36-D32, reinforcement press 12 D32, reinforcement sengkang D13-100 and reinforcement decrease 6D13. At the height of diafragma, diafragma planner 0.800 m, and diafrgama width 0,400 m, used tensile reinforcement 4D13, reinforcement press 2D13, reinforcement sengkang D13-100 and reinforcement decrease 2D13. Side walk using diameter of reinforcement is used D13 and reinforcement distance 10. on the protection of the pole planner, use reinforcement 2D12 and reinforcement geser minimum is D10-200. Thick plate injak 200, using diameter of reinforcement is used D13-100, reinforcement decrease 13D-100. That’s not the result of design, effecintly and effectively compared to the initial planning, in terms of cost and time..